Análise da produção científica a partir dos periódicos "Produção" e "Gestão & Produção" - Rubbo, Priscila (2012)
This study has as purpose to analyze the scientific production published in journals "Production" and "Production Management” in the period of 2001 to 2010. The journals were chosen due to the importance of its publications, and their regular evaluation by Capes, which is currently B2, the most important in the Production Engineering National area. The study tried to draw a profile of publications, to compare the journals with each other and confront a journal with an impact factor bigger than 1. The research was classified as documentary survey. 760 articles were analyzed, 384 about Management and Production, 326 about Production e 50 International Journal of Operations & Production Management. It was attempted to measure variables that could characterize the scientific output of each journal, comparing them through charts and tables. After analyzing the results, among the national magazines that the only variable that is the subject differ. When compared to national journals with international differences are: length, language of articles, amount of keywords, the average years of references and language sources. This way, was concluded that the production of scientific production and Management & Production, are different from regular used as standard because of its concept.